Solve: ("X" + 2)/3 - ("X" + 1)/5 = ("X" - 3)/4 - 1 - Mathematics

Advertisement Remove all ads
Sum

Solve: `("x" + 2)/3 - ("x" + 1)/5 = ("x" - 3)/4 - 1`

Advertisement Remove all ads

Solution

`("x" + 2)/3 - ("x" + 1)/5 = ("x" - 3)/4 - 1`  ...(L.C.M. of 3 and 5 = 15)

`=> (5("x" + 2) - 3("x" + 1))/15 = ("x" - 3 - 4)/4`


`=> (5"x" + 10 - 3"x" - 3)/15 = ("x" - 7)/4`


`=> (2"x" + 7)/15 = ("x" - 7)/4`


⇒ 4(2x + 7) = 15(x - 7)

⇒ 8x + 28 = 15x - 105

⇒ 8x - 15x = -105 - 28

⇒ -7x = - 133

x = `(-133)/(-7)`

∴ x = 19

Concept: Solving Linear Inequations
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (C) | Q 1.1 | Page 169
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×